2010
DOI: 10.1111/j.1474-9726.2010.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Human NK cells display major phenotypic and functional changes over the life span

Abstract: SummaryAging is generally associated with an increased predisposition to infectious diseases and cancers, related in part to the development of immune senescence, a process that affects all cell compartments of the immune system. Although many studies have investigated the effects of age on natural killer (NK) cells, their conclusions remain controversial because the diverse health status of study subjects resulted in discordant findings. To clarify this situation, we conducted the first extensive phenotypic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
233
2
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 285 publications
(282 citation statements)
references
References 49 publications
41
233
2
6
Order By: Relevance
“…Similar observation was made for T cells, in which KIR expression is virtually absent in CD4 and CD8 naive T cells and reaches its maximal level in differentiated effector memory T cells 2, 5, 151, 152. Accordingly, KIR expression is low in less mature cord blood NK and T cells compared with healthy adult control cells 153, 154…”
Section: Kir Gene Expressionsupporting
confidence: 71%
“…Similar observation was made for T cells, in which KIR expression is virtually absent in CD4 and CD8 naive T cells and reaches its maximal level in differentiated effector memory T cells 2, 5, 151, 152. Accordingly, KIR expression is low in less mature cord blood NK and T cells compared with healthy adult control cells 153, 154…”
Section: Kir Gene Expressionsupporting
confidence: 71%
“…The IL-2 induced NK cell proliferation is decreased with aging [81]. Many cytokines and chemokines produced by NK cells are also decreased with aging, such as IL-2, IL-8 [88], while that of IFN-γ seems to be maintained [84]. This decreased production of cytokines contributes to the altered activation of macrophages with aging resulting in decreased microbicidal and tumoricidal activities.…”
Section: Nk Cell Functional Changes With Agingmentioning
confidence: 99%
“…Studies in very healthy elderly populations revealed that the NK cell number tends to increase while the cytotoxicity is not significantly affected [81][82][83] and this is contributing to longevity and successful aging [84,85]. Other studies in unselected elderly populations showed decreased NK cell functions with aging which was associated with higher incidence of infectious diseases [86,87].…”
Section: Nk Cell Functional Changes With Agingmentioning
confidence: 99%
“…The NK cell analysis included NKG2A and NKG2C, which are inhibitory and activating receptors, respectively, binding to the nonclassical human leukocyte antigen (HLA) class I molecule HLA-E (Lanier 1998;Moretta et al 1996). We also assessed the frequency of ILT-2 + and CD57 + NK cells, which both have been demonstrated to have an increasing frequency on NK cells throughout life (Le Garff-Tavernier et al 2010). ILT-2 binds the CMVencoded UL18 protein and is together with CD57 upregulated on terminally differentiated T and NK cells following acute CMV infection (Northfield et al 2005;Lopez-Verges et al 2011).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…In this age group, it is yet uncertain whether an inversed CD4/CD8 ratio corresponds to increased mortality and truly defines an IRP. Since natural killer (NK) cells have an important role in the defense against viral infections and display profound changes throughout the lifespan (Le Garff-Tavernier et al 2010;Biron et al 1996;Beziat et al 2013), we set out to examine whether expansion of CD8 + T cells seen in individuals with an inversed CD4/CD8 ratio is coupled to a parallel skewing of the NK compartment. NK cells belong to the innate arm of the immune system and provide a rapid first line of defense against viral infections and may also contribute to the clearance of transformed cells (Lanier 2005;Vivier et al 2008).…”
Section: Introductionmentioning
confidence: 99%